Two new indole-diterpenoids from the marine-derived fungus Penicillium sp. KFD28. Issue 11 (15th November 2021) - Chen, Ming-Yang; Xie, Qing-Yi; Kong, Fan-Dong; Ma, Qing-Yun; Zhou, Li-Man; Yuan, Jing-Zhe; Dai, Hao-Fu; Wu, You-Gen; Zhao, You-Xing
Abstract: Two new compounds named epipaxilline (1 ) and penerpene J (2 ) were isolated from the marine-derived fungus Penicillium sp. KFD28. Their structures including absolute configurations were determined on the basis of spectroscopic methods and ECD analysis. Compounds 1 and 2 showed inhibitory activities against PTP1B with IC50 values of 31.5 and 9.5 μM, respectively, and compound 2 also showed inhibitory activities against TCPTP with IC50 value of 14.7 μM. Graphical Abstract: UF0001